2003
DOI: 10.1016/s0028-3932(02)00222-1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two commonly used tests of unfamiliar face recognition

Abstract: The Warrington Recognition Memory for Faces (RMF) and the Benton Facial Recognition Test (BFRT) are commercially available tests that are commonly used by clinicians and cognitive neuropsychologists to evaluate unfamiliar face recognition. Yet, it is not clear that a normal score on either instrument demonstrates normal unfamiliar face recognition. Because the RMFs stimuli contain abundant non-internal facial feature information, subjects may be able to score in the normal range without using internal facial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 52 publications
5
108
0
Order By: Relevance
“…The previous studies demonstrated that the capability to discriminate faces from other objects is not affected in temporal lobe lesions, supporting the thesis that such processing is done in the ventral temporal-occipital areas (Allison et al, 1994;Haxby et al, 1996;Kanwisher et al, 1997;Steeves et al, 2006;Pitcher et al, 2007). The neuropsychological tests presently available have nevertheless been unable to detect reliably abnormalities in face recognition (Duchaine and Weidenfeld, 2003;Duchaine and Nakayama, 2004), making it difficult to produce strong inferences about the localizations of occipital lesions from the obtained results.…”
Section: Introductionmentioning
confidence: 81%
“…The previous studies demonstrated that the capability to discriminate faces from other objects is not affected in temporal lobe lesions, supporting the thesis that such processing is done in the ventral temporal-occipital areas (Allison et al, 1994;Haxby et al, 1996;Kanwisher et al, 1997;Steeves et al, 2006;Pitcher et al, 2007). The neuropsychological tests presently available have nevertheless been unable to detect reliably abnormalities in face recognition (Duchaine and Weidenfeld, 2003;Duchaine and Nakayama, 2004), making it difficult to produce strong inferences about the localizations of occipital lesions from the obtained results.…”
Section: Introductionmentioning
confidence: 81%
“…In the present patient both the baseline evaluation and the follow-up assessment revealed a composite clinical picture in which minor defects of configurational face analysis were associated with an impairment to experience visual familiarity for well-known faces, and a substantial impairment to associate visually perceived faces to preserved semantic information about people. This is no room here to tackle the controversial distinction between associative and apperceptive forms of prosopagnosia (De Renzi et al, 1991;Duchaine and Weidenfeld, 2003;s e eGainotti and Marra, 2011, for a recent review), but our data support the hypothesis that ILF is the most critical fibre pathway connecting regions of the core system of face processing (see Haxby et al, 2000;Catani and Thiebaut de Schotten, 2008), as proposed in the past (Benson et al, 1974;Habib, 1986;Kawahata and Nagata, 1989;Meadows, 1974;Takahashi et al, 1995). A damage of rILF would disconnect the occipital face area and the FFA from each other or from regions in the anterior temporal lobe and the precuneus (Catani et al, 2003), thus hampering modulation of right occipital lobe on temporal lobe activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, longer opportunities to process nonface classes could explain their better abilities with these classes. This may be especially true for perceptual tasks in which piecemeal comparison of features is possible (Duchaine & Weidenfeld, 2003). We can test for this possibility by examining RTs for all subjects on all tests.…”
Section: Can Face Selective Processing Be Explained By Slow Reaction mentioning
confidence: 99%